Espaço de direitos é mais que direito a espaço: o processo de urbanização de favelas em Diadema (1983 2008) - Coelho, Marta Cirera Sari (2008)
This dissertation provides a reflection about the process of urbanization of the slum housing in the city of Diadema and know the factors that interfere in the development of this habitational politics process during the period 1983-2008. It will be presented from the right of living with dignity perspective. Introduced by an analysis of the cities formation, especially in the metropolitan areas and concerning the right of living in sustainable cities and the right of citizenship. This study is designated to identify the internal and external factors in the city of Diadema that have influenced the Habitational Politics driven to the slum area from the Rights perspectives. This research was built through documental source, data mining and interviews with spokespersons involved in the Diadema politics. In short, it is indicated by the current analysis that the popular interaction, the continuing of the priority to theses programs between managers were the main factors to the consolidation of the city habitational politics and also for the access to the land and housing in the urbanization process in Diadema slums